Keberlanjutan Budaya dan Keterlibatan Pelanggan pada Hotel Ramah Lingkungan - Baiq Candra Herawati; Handry Sudiartha Athar; Arwin Yafi Rahmatullah; Siti Soraya; Erwin Suhendra (Target : Jurnal Manajemen Bisnis, 2026)
This study examines how perceived cultural sustainability explains green customer engagement ineco-friendly hotels by considering green brand love and cultural identity strength. The study addresses the need for a culturally grounded explanation of green hospitality engagement in island destinations where environmental practices intersect with local culture and identity. A quantitative explanatory design was applied to domestic tourists who had experienced eco-friendly hotel services in Bali, West Nusa Tenggara, and East Nusa Tenggara. Using purposive sampling, 300 valid responses were analyzed. The constructs were measured using seven-point Likert scales, and the data were analyzed using a two- stage CB-SEM procedure with AMOS. Confirmatory factor analysis was used to assess the measurement model, while path analysis with mean-centered interaction terms was used to test direct, mediating, and moderating effects. The findings show that perceived cultural sustainability has a significant direct effect on green customer engagement but does not significantly influence green brand love. Green brand love strongly influences green customer engagement, indicating that emotional attachment remains an important driver of engagement. The mediation effect of green brand love is therefore not the main mechanism linking perceived cultural sustainability and green customer engagement. However, cultural identity strength significantly strengthens the relationship between perceived cultural sustainability and green brand love. This study contributes by showing that cultural sustainability shapes engagement more directly, while cultural identity helps transform cultural sustainability cues into brand affection.